Lack of radiological and clinical benefit over two years of low dose prednisolone for rheumatoid arthritis: results of a randomised controlled trial. Issue 7 (11th June 2004) - Capell, H A; Madhok, R; Hunter, J A; Porter, D; Morrison, E; Larkin, J; Thomson, E A; Hampson, R; Poon, F W
Abstract : Background: Evidence for disease modifying activity of low dose corticosteroid treatment in rheumatoid arthritis is contradictory. Studies showing radiological benefit suggest that continued treatment is required to sustain the effect. Objective: To evaluate the effect of low dose oral prednisolone in early rheumatoid arthritis on disease activity over two years. Design: Double blind placebo controlled trial. Methods: Patients with rheumatoid arthritis, duration <3 years (n = 167), were started on a disease modifying antirheumatic drug (DMARD; sulphasalazine) and allocated by stratified randomisation to prednisolone 7 mg/day or placebo. Primary outcome measure was radiological damage, assessed by the modified Sharp method. Clinical benefit was a secondary outcome. A proactive approach to identifying and treating corticosteroid adverse events was adopted. Patients who discontinued sulphasalazine were offered an alternative DMARD. Results: 90 of 257 patients eligible for the study refused to participate (more women than men). Of those enrolled, 84% were seropositive for rheumatoid factor, median age 56 years, median disease duration 12 months, female to male ratio 1.8:1. Prednisolone was given to 84 patients; of these 73% continued prednisolone and 70% sulphasalazine at 2 years. Of the 83 patients on placebo, 80% continued placebo and 64% sulphasalazine at 2 years. There were no significant differences in radiological score or clinical and laboratory measures at 0 and 2 years. Conclusions: Low dose prednisolone conferred no radiological or clinical benefit on patients maintained on a DMARD over two years. Low dose corticosteroids have no role in the routine management of rheumatoid arthritis treated with conventional disease modifying drugs.